Numerical study on the flow and heat-transfer characteristics of horizontal finned-tube falling-film evaporation: Effects of liquid column spacing and wettability. (1st June 2022) - Cao, Chuanpeng; Xie, Lixin; He, Xuan; Ji, Qingyuan; Zhao, Han; Du, Yawei
Highlights: A 3D CFD model was established to capture the microscopic gas-liquid interface. The microscopic falling film flow behavior of the finned tube was demonstrated. The heat transfer coefficient and falling-film distribution were exhibited. The effect of liquid column spacing on heat transfer performance was implemented. The heat transfer characteristics with variation of contact angle was revealed. Abstract: The horizontal finned-tube falling-film evaporator has been successfully used in desalination and other industries. An effective three-dimensional Computational Fluid Dynamics (CFD) model was established to investigate the falling film and heat transfer characteristics of the horizontal finned-tube, and the numerical results were verified by experimental data. The influences of the liquid column feed spacing ( S ) and Reynolds number ( Re ) on the hydrodynamic characteristics, film thickness distribution and heat transfer characteristics for the finned-tube falling-film evaporation were explored. The fluid behavior and heat transfer performance with the variation of contact angle (α) were further revealed. At low Re, the liquid films fail to fully cover the tube surface with appearance of dry wall, causing the substantial decrease in wetting ratio and heat transfer performance. When Re  = 684, the wetting ratio and average heat transfer coefficient were greatly improved, reaching 0.96 and 7922 W/m 2 ·K, respectively. Heat flux has little effect on heat transfer performance. Additionally, as α increases, both the wetting ratio and the average heat transfer coefficient decrease. The average heat transfer coefficient drops from 8052 W/m 2 K at 0° to 3692 W/m 2 K at 80°. Furthermore, under different Re and α, smaller S exhibits better wetting properties and heat transfer characteristics.